Solutions to exercises [for] Chemistry : the central science / Roxy Wilson ... [et al] - Bursten, Bruce Edward
Enhances the nearly 2300 end-of-chapter exercises by providing documented solutions. The manual cautions that some solutions may vary due to differences in problem-solving methods.